The Physicochemical Effects of Plasma Jet Treatment on Musa Acuminata - Wahab, Nur Syafika; Mohamad Fauzi, Siti Fatimah Zaharah (Enhanced Knowledge in Sciences and Technology, 2025)
In recent years, there has been increasing interest in non-thermal food preservation technologies to address the growing demand for fresh produce with better quality and extended shelf life. Traditional methods such as heat treatment, refrigeration, and chemical preservation have limitations, including nutrient loss, flavour alteration, and the production of undesirable by-products. In addition, concerns about the environmental impact of these methods have driven the search for more sustainable solutions that can preserve food quality while minimizing these issues. Cold Atmospheric Plasma (CAP) treatment has emerged as a promising non-thermal technology with the potential to improve the quality and shelf life of fruits and vegetables. In this study, the effects of CAP treatment on the physicochemical properties of ripe Cavendish bananas (Musa acuminata) were systematically evaluated. Bananas were exposed to CAP for different durations (0, 5, 10, and 25 minutes) using a cold argon plasma jet system, and several key parameters which are pH, firmness, moisture content, and antioxidant activity were analysed. The results showed that extended CAP treatment significantly increased the firmness of the bananas, with the highest firmness achieved after 25 minutes. While moisture content decreased slightly with longer exposure, antioxidant activity was notably enhanced, especially with a 10-minute treatment, suggesting that moderate plasma exposure can stimulate beneficial antioxidant responses. Though the pH of the bananas varied with treatment duration, no clear trend emerged. These findings indicate that CAP treatment can effectively modify the physicochemical properties of bananas, improving both texture and antioxidant activity. This suggests that CAP could be a viable non-thermal alternative for enhancing postharvest quality and extending the shelf life of bananas, offering a sustainable solution to the challenges of food preservation and spoilage reduction.